1992
DOI: 10.1152/ajpheart.1992.263.6.h1963
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide production within cardiac myocytes reduces their contractility in endotoxemia

Abstract: We investigated whether increased nitric oxide (NO) synthase activity within cardiac myocytes contributes to the depressed cardiac contractility observed in endotoxic shock. Isolated ventricular myocytes were studied to examine the effects of substrates and inhibitors of NO synthase on myocyte contractility. When stimulated electrically, the resting length of myocytes from control animals shortened by 5.3 +/- 0.3% (means +/- SE, n = 32). Baseline contraction of myocytes from endotoxin-treated animals was reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
129
1
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(135 citation statements)
references
References 0 publications
2
129
1
3
Order By: Relevance
“…Thus we would expect that inhibition of endocardial or myocardial NO synthesis by L-NAME would increase myocardial contractility if it is to have any direct effect. In fact, previous work has shown that administration of NO synthase inhibitors to isolated cardiac myocytes from healthy animals neither augments nor reduces their contractility (Amrani et al, 1992;Brady et al, 1992). In our experiments cardiac output decreased following inhibition of NO synthesis and was completely restored by nicardipine which is a vasodilator with little or no direct inotropic action (Rousseau et al, 1985).…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Thus we would expect that inhibition of endocardial or myocardial NO synthesis by L-NAME would increase myocardial contractility if it is to have any direct effect. In fact, previous work has shown that administration of NO synthase inhibitors to isolated cardiac myocytes from healthy animals neither augments nor reduces their contractility (Amrani et al, 1992;Brady et al, 1992). In our experiments cardiac output decreased following inhibition of NO synthesis and was completely restored by nicardipine which is a vasodilator with little or no direct inotropic action (Rousseau et al, 1985).…”
Section: Discussioncontrasting
confidence: 41%
“…This mechanism may contribute to myocardial dysfunction in endotoxic shock (Brady et al, 1992) and in dilated cardiomyopathy (de Belder et al, 1993). Thus we would expect that inhibition of endocardial or myocardial NO synthesis by L-NAME would increase myocardial contractility if it is to have any direct effect.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of NO on SR Ca z+ release could account for the previously observed NO-induced force reduction in both skeletal [5] and cardiac muscle [3,4]. Whether or not NO has a role in regulating muscle contraction on a twitch-by-twitch (or beatby-beat) basis is too early to speculate.…”
Section: Resultsmentioning
confidence: 97%
“…More recently, NO has been implicated in cytokine-and endotoxin-evoked decreases in cardiac contractility [3,4] and found to depress contractile function in fast skeletal muscle where the brain type constitutive NO-synthase (NOS) has been shown to be expressed [5]. The reduction of skeletal muscle contractile force by NO was only partially ascribable to its stimulatory effect on guanylate cyclase [5], the often reported signaling pathway in NO action [1,2,6].…”
Section: Introductionmentioning
confidence: 99%
“…11 Nitric oxide can exert a negative inotropic effect in cultured guinea pig myocytes, an effect augmented by enhanced nitric oxide production induced by endotoxin. 12 In addition, nitric oxide can also affect diastolic function by quickening ventricular relaxation and enhancing chamber passive relaxation. [13][14][15] The actions of nitric oxide on the coronary circulation have been well studied.…”
Section: Introductionmentioning
confidence: 99%